The Usage of Influenza Vaccine to Prevent Seasonal Influenza during Pandemic COVID-19 - Levani, Yelvi; Paramita, Ayu Lidya (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2021)
Influenza is an acute respiratory disease caused by influenza virus. Influenza can affect million people in every year and causing morbidity. Some of cases can be severe and need hospitalized, especially in elderly people. Influenza is an airborne disease and can spread rapidly. Every seasonal flu can be different because Influenza virus do mutation. Influenza vaccine can reduce morbidity and mortality. There are two types of influenza vaccine; live attenuated influenza virus (LAIV) and inactivated influenza virus (IIV). The newest type of influenza vaccine consists four types of virus (quadrivalent), therefore it gives more protection compared to the older one. Influeza vaccine is still recommended during pandemic COVID-19 because it can prevent co-infection between Influenza and COVID-19. In addition, it can reduce the morbidity and mortality during pandemic COVID-19.